Sifat Fisik Daging Domba yang Diberi Perlakuan Stimulasi Listrik Voltase Rendah dan Injeksi Kalsium Klorida - T Suryati; M Astawan; T Wresdiyati (Faculty of Animal Science, Bogor Agricultural University, 2004)
Effect of low voltage electrical stimulation (LVES; 45 volt, 3 amps for approx 100 sec) and calcium chloride (CaCl2) injection on physical properties of meat were evaluated. Six mutton were devided into 3 groups. One carcass of each group was subjected to within 30 min postmortem (PM). After LVES, longissimi thoracis et lumbarum muscles were removed and treated: without CaCl2 injection, CaCl2 injection (200 mM, 5% w/w) at about 2 h and 24 h PM. Samples were stored in vacuum pack at 1 + 10 C. Physical properties evaluated were Warner-Bratzler (WB) shear force, cooking loss and sarcomere length. The LVES had no significant effect on WB shear force, cooking loss and sarcomere length. There wasn't interaction effect between LVES and CaCl2 injection on WB shear force, cooking loss and sarcomere length. CaCl2 injection decreased sarcomere length (P